2022
DOI: 10.1186/s13018-022-03450-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cervical spine motion on displacement of posterolateral annulus fibrosus in cervical spondylotic radiculopathy with contained posterolateral disc herniation: a three-dimensional finite element analysis

Abstract: Background Previous studies on dynamic impingement of nerve root in cervical spondylotic radiculopathy (CSR) have focused on effect of cervical spine motion (CSM) on dimensional changes of intervertebral foramen. However, there are few studies to investigate effect of CSM on displacement of posterolateral intervertebral disc until now. The present study aimed to investigate effect of CSM on displacement of posterolateral annulus fibrosus (AF) in CSR with contained posterolateral disc herniation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Several prior studies have incorporated layered annulus models (Schmidt et al, 2006). By utilizing these advanced modeling techniques, we aimed to better represent the complex behavior of the annulus fibrosus to compare with the previous biomechanical models, which often simplify the annulus fibrosus by assuming it to be a homogeneous and isotropic material (Ye et al, 2022). These studies have shown that the annulus fibrosus exhibits Frontiers in Bioengineering and Biotechnology frontiersin.org significant regional variations in composition, fiber orientation, and mechanical properties (Acaroglu et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies have incorporated layered annulus models (Schmidt et al, 2006). By utilizing these advanced modeling techniques, we aimed to better represent the complex behavior of the annulus fibrosus to compare with the previous biomechanical models, which often simplify the annulus fibrosus by assuming it to be a homogeneous and isotropic material (Ye et al, 2022). These studies have shown that the annulus fibrosus exhibits Frontiers in Bioengineering and Biotechnology frontiersin.org significant regional variations in composition, fiber orientation, and mechanical properties (Acaroglu et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate thresholding generated a lumbar spine mask by excluding soft tissue, followed by cavity filling and mask smoothing to reconstruct the initial L4-L5 3D model in STL format ( Li et al, 2022b ). Geomagic Studio was used for mesh optimization, encompassing feature removal, noise reduction, and other preprocessing steps to optimize the model structure ( Ye et al, 2022 ). After employing “Grid Doctor” for validation and refinement, thin bone tissue was removed, and the “migration of the whole” technique established cancellous bone.…”
Section: Methodsmentioning
confidence: 99%